Iatrogenic lesions of peripheral nerves. (16th April 2015) - Löscher, W. N.; Wanschitz, J.; Iglseder, S.; Vass, A.; Grinzinger, S.; Pöschl, P.; Grisold, W.; Ninkovic, M.; Antoniadis, G.; Pedro, M.T.; König, R.; Quasthoff, S.; et al.
<x xml:space="preserve">Abstract</x> Iatrogenic nerve lesions (INLs) are an integral part of peripheral neurology and require dedicated neurologists to manage them. INLs of peripheral nerves are most frequently caused by surgery, immobilization, injections, radiation, or drugs. Early recognition and diagnosis is important not to delay appropriate therapeutic measures and to improve the outcome. Treatment can be causative or symptomatic, conservative, or surgical. Rehabilitative measures play a key role in the conservative treatment, but the point at which an INL requires surgical intervention should not be missed or delayed. This is why INLs require close multiprofessional monitoring and continuous re‐evaluation of the therapeutic effect. With increasing number of surgical interventions and increasing number of drugs applied, it is quite likely that the prevalence of INLs will further increase. To provide an optimal management, more studies about the frequency of the various INLs and studies evaluating therapies need to be conducted. Management of INLs can be particularly improved if those confronted with INLs get state‐of‐the‐art education and advanced training about INLs. Management and outcome of INLs can be further improved if the multiprofessional interplay is optimized and adapted to the needs of the patient, the healthcare system, and those responsible for sustaining medical infrastructure.